1988
DOI: 10.1159/000138371
|View full text |Cite
|
Sign up to set email alerts
|

Protection by Opioids against Gastric Lesions Caused by Necrotizing Agents

Abstract: The synthetic opioid met-enkephalin analog [D-Ala2, MePhe4, Met(0)5ol] enkephalin (DAMME) and the opiate morphine injected intraperitoneally to rats at doses of 0.5–2 and 5–20 mg/kg, respectively, showed a protective effect on gastric damage induced by oral administration of necrotizing agents (0.6 NHCl or 0.2 NNaOH solutions, 1 ml/rat). The protection was prevented by naltrexone (10 mg/kg s.c), an opioid antagonist with long-lasting activity. Histological sections of mucosal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…11 Studies have shown that opioid receptor activation by exogenous agonists can facilitate a protective effect against hypoxia, ischemia, cold, or an acidic environment. [12][13][14] More recently, we published that morphine pretreatment can provide significant retinal neuroprotection against acute ischemic 15 and glaucomatous injury, 16 and this neuroprotection is mediated, in part, via inhibition of TNF-a production. 16,17 However, the neuroprotective roles of d-opioid receptors against glaucomatous injury have remained fully unexplored.…”
mentioning
confidence: 99%
“…11 Studies have shown that opioid receptor activation by exogenous agonists can facilitate a protective effect against hypoxia, ischemia, cold, or an acidic environment. [12][13][14] More recently, we published that morphine pretreatment can provide significant retinal neuroprotection against acute ischemic 15 and glaucomatous injury, 16 and this neuroprotection is mediated, in part, via inhibition of TNF-a production. 16,17 However, the neuroprotective roles of d-opioid receptors against glaucomatous injury have remained fully unexplored.…”
mentioning
confidence: 99%
“…9 In other systems, opioid-receptor activation by exogenous agonists (like endogenous opioid-induced preconditioning) has been shown to facilitate a protective effect against hypoxia, ischemia, cold, or an acidic environment. [10][11][12] Recently, we published novel findings that morphine pretreatment can provide significant retinal neuroprotection against acute ischemic injury, 8 and this neuroprotection is mediated in part, via inhibition of TNF-a production. 13 TNF-a is a proinflammatory cytokine that is rapidly upregulated in several neurodegenerative disorders, such as multiple sclerosis, Parkinson disease, Alzheimer disease, and glaucoma.…”
mentioning
confidence: 99%
“…or intraperitoneal (i.p.) administra tions of morphine and a synthetic met-enkephalin analogue (FK33-824) were effica cious in preventing experimental ulcers in the rat [5,6], The findings seemed to be related to an involvement of opioid receptors because the blockade of these receptors, with naloxone [4,7] or naltrexone [8], prevented the gastric protection induced by morphine or FK33-824 [4]. It has also been described that both cen tral and peripheral p-and 5-opioid receptors were the functionally important species that could mediate these effects [9.…”
Section: Introductionmentioning
confidence: 97%